Relationship between anterior segment biometry and primary angle-closure glaucoma in Hubei region: a retrospective case-control study - Wang, Shan; Zhang, Han; Yang, Wanju; Zhang, Ying; Qin, Hui; Wang, Man; Lei, Xinlan; Yang, Kuiliang; Zhang, Hong; Xing, Yiqiao (Frontiers in Medicine, 2024)
Objective To investigate the pathogenesis of Primary Angle-Closure Glaucoma (PACG) and its relationship with the anatomical structure of the anterior segment by obtaining biometric parameters using the IOL-Master 700. Methods A retrospective case–control study was conducted. Clinical data from 39 PACG patients and 40 normal controls treated at the Aier Eye Hospital affiliated with Wuhan University from January to December 2022 were collected. Anterior chamber depth (AC), white-to-white (WTW), lens thickness (LT), central corneal thickness (CCT), axial length (AL), corneal curvature (K1), corneal curvature (K2), and lens position (LP) were measured using the IOL-Master 700 to analyze the characteristics and differences in the anterior segment structure of both groups. Statistical methods included independent sample t-tests and logistic regression analysis. Results Significant differences were found in the anterior segment biometric parameters between PACG patients and normal controls (p < 0.05). Anterior chamber depth, white-to-white, lens thickness, central corneal thickness, axial length, and K2 were all related to the occurrence of PACG (p < 0.05). The occurrence of PACG was negatively correlated with ACD, CCT, and AL (OR = 0.12–0.64, p < 0.05), and positively correlated with LT. Conclusion Compared to the normal control group, PACG patients in the Hubei region have a smaller anterior segment space, narrower angles, thicker lens, thinner cornea, shorter axial length, flatter cornea, and more anteriorly positioned lens.